2009
DOI: 10.1126/science.1173826
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Turtle Body Plan by the Folding and Creation of New Muscle Connections

Abstract: The turtle shell offers a fascinating case study of vertebrate evolution, based on the modification of a common body plan. The carapace is formed from ribs, which encapsulate the scapula; this stands in contrast to the typical amniote body plan and serves as a key to understanding turtle evolution. Comparative analyses of musculoskeletal development between the Chinese soft-shelled turtle and other amniotes revealed that initial turtle development conforms to the amniote pattern; however, during embryogenesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(153 citation statements)
references
References 25 publications
8
141
0
1
Order By: Relevance
“…More recently, we have added another vertebrate species, the Chinese soft-shell turtle (Pelodiscus sinensis), to the analysis (Wang et al, 2013). Although the turtle has a very different body plan to that of other vertebrates (Nagashima et al, 2009), we found that the most conserved embryonic period between turtle and chicken in terms of expression profiles matched the same vertebrate phylotypic period that had been identified previously (Irie and Kuratani, 2011) (Fig. 2C).…”
Section: The Morphological Features Of the Phylotypic Periodmentioning
confidence: 61%
“…More recently, we have added another vertebrate species, the Chinese soft-shell turtle (Pelodiscus sinensis), to the analysis (Wang et al, 2013). Although the turtle has a very different body plan to that of other vertebrates (Nagashima et al, 2009), we found that the most conserved embryonic period between turtle and chicken in terms of expression profiles matched the same vertebrate phylotypic period that had been identified previously (Irie and Kuratani, 2011) (Fig. 2C).…”
Section: The Morphological Features Of the Phylotypic Periodmentioning
confidence: 61%
“…As we have shown here, embryos of a pleurodiran turtle have the rib development axially arrested, with a conserved topographical relationship of different anatomical elements in the same position as other turtles (Hirasawa et al, 2014). This suggests that the development of the shell by the axial arrest of the rib cage and the folding of the body wall is the mechanism by which the carapace was formed in the common ancestors of turtles (Hirasawa et al, 2014, Nagashima et al, 2009. The turtle last common ancestor would probably have had epidermal scutes over the endoskeleton scaffold of the carapace, but the developmental module underlying the formation of the scutes comes later than the CR induction in development , and whether it has been indeed conserved between cryptodiran and pleurodiran still needs further research.…”
Section: Wnt Pathway and The Evolutionary Origin Of The Carapacial Ridgementioning
confidence: 99%
“…Compared with the general tetrapod bauplan, the turtle skeleton is radically different: in the turtle the ribs remain in the dorsal part and grow laterally, instead of ventrally, due to a process that has been called axial arrest . Eventually, unlike in the rest of tetrapods, the rib cage remains open and the shoulder girdle becomes underneath them by folding of the body wall ('Folding Theory'; Kuratani et al, 2011, Nagashima et al, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Several rather limited taxons such as chelonians and crocodilians have received some attention recently, for very specific purposes (Green et al, 2014, Milinkovitch et al, 2013, Nagashima et al, 2009, Shaffer et al, 2013, Wang et al, 2013, yet the importance of Squamata is certainly not reflected in the number of species used efficiently at the bench, despite the recent releases of genome sequences for the green anole lizard (Alfoldi et al, 2011), the Burmese python (Castoe et al, 2013) the king cobra (Vonk et al, 2013) or other snakes (Gilbert et al, 2014), as well as several high quality transcriptomes (see e.g. (Schwartz et al, 2010, Tzika et al, 2011.…”
Section: 'Snakes' As Model Organisms?mentioning
confidence: 99%